Pengaruh Pemanfaatan Audio Visual Dalam Pengembangan Psikoreligius Warga Binaan Wanita di Lapas Kelas II A Curup Kabupaten Rejang Lebong - Fadila, Fadila (ISLAMIC COUNSELING: Jurnal Bimbingan Konseling Islam, 2018)
This study aims to explain (a) how Psychoreligius wargabinaan woman class II A Curation Correctional, (b) Audiovisual Utilization in developing Psikoreligius wargabinaan woman class II A Curas Curup, (c) Effect of Audiovisual utilization in psychoreligius development of woman class II Curation Service. This research uses quantitative research method with approach using quasi experiment method. In the early stages used pre-test to know psychoreligius wargabinaan woman in prison class II A Curup. Then will be treated (treatment) using audio visual media in a certain period. Then measured for the second time called post-test. The research design used in this study was pretest-posttes with one kind of treatment. The results of this study illustrate that: the psycho-religious womens wargabinaan in prison influence / improve after using audiovisual utilization.